The Future Perspectives of Redefining the Resection Margin Status in Different Cancers of Pancreas - Elshaer, Ahmed; El-Sayed, Tamer; Dasgupta, Dowmitra (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: The interest towards the assessment of circumferential resection margins(CRM) in pancreatic cancers has been evolving over last years. Whilst several studies investigated the influence of R1-resections on survival, not many studies evaluated the prognostic value of each resection margin. In this study, we examined the different resection margins to better understand their prognostic implications on overall survival. Methods: This prospective study included a cohort of patients who had pancreaticoduodenectomy for cancer purposes at our institution from 2008 till 2013. Median follow-up was 6 years. Involved margins in R1-resections were further classified into anatomical margins (anterior, posterior and circumferential margins) and surgical margins (vascular/medial margins and transection margins). Overall survival was assessed for each specific resection margin. Results: 134 patients were included with median age 66 years. R1-resection was done in 54% of patients(n=72/134). Median survival of R0-resection group was 6.3 years, compared to 1.9 years for R1-resection group(p-value 0.001). Vascular (surgical) margins had the lowest survival rate (1.7years) compared to anatomical margins (anterior, posterior and circumferential margins) with 3.6, 2.2 and 2.1 years respectively (p-value 0.02). On multivariate analysis; lymph node involvement and vascular resection were the only factors to correlate significantly with poor survival. Conclusion: Whilst the new pathological protocols advised to perform rigorous margin assessment of CRM, the prognostic value of each resection margin is still unclear. This study showed variation of survival across different resection margins with inferiority towards vascular (surgical) margins. This supported the need of redefining R1-margins in the future pathological classifications according to their different prognostic impacts.